FENOMENA UNJUK KERJA (PERFORMANCE) POMPA MERCURY MP-700 SUSUNAN TUNGGAL, SERI DAN PARALEL - Wardianto, Dedi (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Ones that supports a learning process in the course is the completeness of facilities andinfrastructure. The author design the performance test equipment of single, series andparallel pump, to increase the level of students understanding in the MechanicalEngineering Department of Muhammadiyah University, West Sumatra. Two pump used isa kind of aquarium pump in the same type (MERCURY MP-700). Power is10 watts, headis 90 cm and a maximum capacity is 700 l / h. Installation arrangement made as small aspossible so it is easily removed, placed on a lab table when using it. As a test resultsobtained, the performance of the two pumps are relatively similar. After compared with thetheoretical formulation of the laws Bernoulli, the experiment result is reduce that of theruducing of the flow rate accumulated in the lower elevations head, for a reduction of theflow rate in series arrangement is the head height is not too large, while the parallelarrangement is a increase in the height of maximum head. The research isnot able to showthe lower head since the flow capacites is measure using a scaled glass and stopwatch at aheight of 30 cm.Keywords: performance pump, head, flow capacity, a single, serial and parallel.